Β2 Adrenergic receptors mediate important electrophysiological effects in human ventricular myocardium. Issue 1 (1st July 2001) - Lowe, M D; Rowland, E; Brown, M J; Grace, A A
Abstract : OBJECTIVE: To define the effects of β2 adrenergic receptor stimulation on ventricular repolarisation in vivo. DESIGN: Prospective study. SETTING: Tertiary referral centre. PATIENTS: 85 patients with coronary artery disease and 22 normal controls. INTERVENTIONS: Intravenous and intracoronary salbutamol (a β2 adrenergic receptor selective agonist; 10–30 μg/min and 1–10 μg/min), and intravenous isoprenaline (a mixed β1 /β2 adrenergic receptor agonist; 1–5 μg/min), infused during fixed atrial pacing. MAIN OUTCOME MEASURES: QT intervals, QT dispersion, monophasic action potential duration. RESULTS: In patients with coronary artery disease, salbutamol decreased QTonset and QTpeak but increased QTend duration; QTonset –QTpeak and QTpeak –QTend intervals increased, resulting in T wave prolongation (mean (SEM): 201 (2) ms to 233 (2) ms; p < 0.01). There was a large increase in dispersion of QTonset, QTpeak, and QTend which was more pronounced in patients with coronary artery disease—for example, QTend dispersion: 50 (2) ms baseline v 98 (4) ms salbutamol (controls), and 70 (1) ms baseline v 108 (3) ms salbutamol (coronary artery disease); p < 0.001. Similar responses were obtained with isoprenaline. Monophasic action potential duration at 90% repolarisation shortened during intracoronary infusion of salbutamol, from 278 (4.1) ms to 257 (3.8) ms (p < 0.05). CONCLUSIONS: β2 adrenergic receptors mediate important electrophysiological effects in human ventricular myocardium. The increase in dispersion of repolarisation provides a mechanism whereby catecholamines acting through this receptor subtype may trigger ventricular arrhythmias.